2004
DOI: 10.1017/s0031182004006389
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term temporal stability of the helminth component community structure in bank voles (Clethrionomys glareolus) from the Mazury Lake District region of Poland

Abstract: (2005) Medium-term temporal stability of the helminth component community structure in bank voles (Clethrionomys glareolus) from the Mazury Lake District region of Poland. Parasitology, 130 (2). pp. 213-228. ISSN 0031-1820Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/29204/1/Bajer%20et%20al%202005%20cleths%20medium %20term%20helm%20stability%20in%20cleths.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 37 publications
7
69
0
Order By: Relevance
“…Poland (Bajer et al 2005). Based on a study conducted in 1999, we also reported detectable and quantifiable differences in community structure of helminths in voles living in 3 semi-isolated woodland habitats in the same region .…”
Section: Introductionmentioning
confidence: 67%
“…Poland (Bajer et al 2005). Based on a study conducted in 1999, we also reported detectable and quantifiable differences in community structure of helminths in voles living in 3 semi-isolated woodland habitats in the same region .…”
Section: Introductionmentioning
confidence: 67%
“…How do common versus rare species contribute to infracommunity structure ? Our earlier work showed some temporal stability in helminth infracommunities in bank voles from one of our study sites (Urwitałt ; see Bajer et al 2005) leading us to predict that, with age and sex effects taken into consideration, differences between sites would be a major factor in explaining variation in our measures of infracommunity structure, whereas time would be relatively less important. In this paper we test this idea.…”
Section: Introductionmentioning
confidence: 75%
“…Numerous studies on the parasite fauna of rodents concerning various aspects, such as the impact of extrinsic and intrinsic factors on helminth interactions, have been carried out in recent years (Bajer et al, 2005;Behnke et al, 2005;Eira et al, 2006;Fuentes et al, 2007). Apart from ecological aspects, relevant information about the taxonomical status or host-parasite relationship became apparent during investigations on the helminth fauna of rodents (Feliu et al, 2000;Hildebrand et al, 2004;Hildebrand et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies show that the possible parasite spectrum has not yet been completely described (Haukisalmi & Henttonen, 2001Hildebrand et al, 2007b). The number of nematode species reported in murid or arvicolid rodents is inconstant, differing between sites and depending on climatic changes (Abu-Madi et al, 2000;Bajer et al, 2005;Behnke et al, 2008). According to Pojmanska (1998), the nematode fauna of M. glareolus in Poland is represented by 13 species, though some statements are still debatable (Tenora & Meszaros, 1975;Hildebrand et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation